Upaya Pemenuhan Istirahat Dan Tidur Pada Ibu Hamil Trimester III - Dewiani, Chika; , Sulastri, S.Kp., M.Kes (2017)
Background: in effort to achieve the MGD's target in health sector namely to increase the intensity of health by giving particular attention to care Mother and Child Health (MCH). During pregnancy thing to note is the basic requirement in maintaining physiological and psychological balance. As for the psychological changes in the third trimester pregnant women seem more increased compared to the previous trimester. The changes during pregnancy will affect the fulfillment of bed rest difficulty to determine comfortable sleeping position, hormonal changes also cause psychological changes so that pregnant women have sleeping difficulty. The impact of sleep disorders and sleep quality poses a risk to the fetus that is preterm birth, gestational hypertension and depression during childbirth. To reduce sleep disturbances nurses can perform some actions such as progressive relaxation, massage, hypnosis, yoga, music therapy, breathing techniques, lateral position, and a warm bath. This can cause the mother to be relaxed.Objective: provide measures in order to increase the bed rest need in the third trimester pregnant women.Methods: The descriptive method with case study approach that is the scientific method is to collect data, analyze the data and draw data's conclusions.Result: After the action during 3 Days nursing home visits this scientific paper are expected to improve patient compliance and bed rest gradually.